Effects of quenching and tempering heat treatment on microstructure, mechanical properties, and fatigue crack growth behavior of 51CrV4 spring steel. (9th September 2021) - Lai, Chaobin; Huang, Wei; Li, Shengci; Liu, Tao; Lv, Ruiguo; Tang, Xiaoyong; Yu, Jianlin
Abstract: Herein, the microstructure, mechanical properties, and fatigue crack growth (FCG) behavior of 51CrV4 spring steels under different quenching and tempering heat treatment were studied. Results show that tempering temperature would not affect the prior austenite grain (PAG) size, while quenching temperature has a great influence on it; the volume fraction of carbide precipitates decreased with increasing quenching temperature. The width of martensite lath has little relationship with the prior austenite grain size. The mechanical properties of the investigated steels decreased with an increasing tempering temperature. Tempering temperature had a greater influence on the fatigue crack growth behavior compared with quenching temperature. The FCG of all the investigated steels were well interpreted by Paris model. When the quenching temperature was 840 °C, the stable expanding stage of the fatigue fracture was representative fatigue striations, fatigue steps and secondary cracks; multiple failure mechanisms coexisted in the rapid expanding stage; the fracture morphology of unstable failure stage was mainly dimples. When the quenching temperature increased to 880 °C and 920 °C, quasi-cleavage was observed in all the stages compared with the samples quenched at 840 °C. Secondary cracks, fatigue steps and crack closure could retard the FCG rate by consuming the driving force near the tip of fatigue crack.